Intersexual Agonism in Gray Langurs Reflects Male Dominance and Feeding Competition - Koenig, Andreas; Miles, Angela; Riaz, Durr-E-Ajam; Borries, Carola (Frontiers in Ecology and Evolution, 2022)
Male-female agonism varies throughout the primate order with males often dominating females, especially in sexually dimorphic species. While intersexual agonism has been attributed to sexually coercive contexts, it can also occur for other reasons and intersexual dominance may be influenced by the adult sex ratio. If the proportion of males is high, certain males will regularly lose against other males. Loser-effects may then pave the way for some females to dominate these males, an effect that has been described in a few primate species. Here we investigated the frequency, general style, and context of agonism among gray langurs (Semnopithecus spp.). Data were collected at two study sites, at Jodhpur, India (one group), and at Ramnagar, Nepal (two groups). The adult sex ratio varied between 0.077 and 1.000 males to females. At both sites, data on agonistic interactions (aggression and submission) were collected in continuous focal animal and ad libitum sampling techniques during 1,945 contact hours (including 1,220 focal animal hours, total). Although aggression intensity was low, high directional consistency and the rare occurrence of counteraggression suggested a despotic dominance style, a likely prerequisite for dominance effects based on adult sex ratio. Aggression by females against males was very rare and mainly occurred in the defense of offspring. We found little evidence for partial female dominance regardless of adult sex ratio. In a few cases in which a female had a higher dominance index than a male, she did not dominate this male in dyadic encounters. Agonism by males directed at females occurred mainly in a feeding context while male policing and a sexual context were both rare. The latter was mostly restricted to females after they had harassed a sexual interaction or after they had behaved proceptively toward a male. Our study suggests that across species the effect of adult sex ratio on female dominance might be more variable than previously suggested. The fact that most agonism between males and females occurred over food identifies intersexual feeding competition as a new research avenue with potentially important consequences for existing ideas on the costs and benefits of group life and composition.